2014
DOI: 10.1186/2052-336x-12-95
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some operational parameters on the arsenic removal by electrocoagulation using iron electrodes

Abstract: Arsenic contamination of drinking water is a global problem that will likely become more apparent in future years as scientists and engineers measure the true extent of the problem. Arsenic poisoning is preventable though as there are several methods for easily removing even trace amounts of arsenic from drinking water. In the present study, electrocoagulation was evaluated as a treatment technology for arsenic removal from aqueous solutions. The effects of parameters such as initial pH, current density, initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 38 publications
2
26
1
3
Order By: Relevance
“…The result from this study is in agreement with Phan et al [20] who achieved the highest COD and color removal efficiency in coffee wastewater without the addition of agitation. However, it differed with the results from several studies where the optimum speed was 300 rpm for cadmium removal [26], 150 rpm for arsenic removal [27], COD removal in poultry slaughterhouse wastewater [28], and boron removal [29]. In our study, the increase of COD in the effluent when the EC treatment applied stirring would be due to the breaking of flocs, and some floating sludge returning back to the solution under stirring.…”
Section: -contrasting
confidence: 95%
“…The result from this study is in agreement with Phan et al [20] who achieved the highest COD and color removal efficiency in coffee wastewater without the addition of agitation. However, it differed with the results from several studies where the optimum speed was 300 rpm for cadmium removal [26], 150 rpm for arsenic removal [27], COD removal in poultry slaughterhouse wastewater [28], and boron removal [29]. In our study, the increase of COD in the effluent when the EC treatment applied stirring would be due to the breaking of flocs, and some floating sludge returning back to the solution under stirring.…”
Section: -contrasting
confidence: 95%
“…Water is used in daily activities, which in turn increases the need for efficient wastewater treatment facilities. Due to rapid industrialization, a large quantity of polluted water is generated every year by different industries such as textile (Zheng et al 2012), leather (Natarajan et al 2013), pharmaceutical (Farhadi et al 2012;Boroski et al 2009), heavy metal (Al Aji et al 2012), cadmium removal (Bayar et al 2013;Yilmaz et al 2012), arsenic (Can et al 2012(Can et al , 2014, dairy processing (Idris et al 2012), paint (Singh et al 2015), petroleum (Zhou et al 2012), pulp and paper (Bengtsson et al 2008;Pokhrel and Viraraghavan 2004), distillery (Lucas et al 2009), fertilizer (Srivastava et al 1996), tannery (Houshyar et al 2012), landfill (Wu et al 2011), bakers yeast (Gengec et al 2012), food processing (Pocostales et al 2012), biodiesel (Ngamlerdpokin et al 2011) and olive packaging industries (García-García et al 2011;Kul et al 2015), Pistachio processing industry Fil et al 2014), etc. The pulp and paper industry is a large consumer of fresh water and an important source of wastewater (Ashrafi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2, for the given time (t=55 min), the removal efficiency appeared to increase significantly with increase in current density. Can et al (2012) demonstrated that arsenic removal efficiency reached to 98 % with increasing current density. This is attributed that with increasing current density, the rate of Al +3 ions passing from soluble aluminum electrodes to the solution increases.…”
Section: Resultsmentioning
confidence: 96%